An analytical economic study of the relationship between exchange rate changes in Algeria and inflation during the period 1991-2023 - abi, walid; djeddi, amina (Journal of Research in Finance and Accounting, 2024)
The study aimed to identify the relationship between the dinar exchange rate and the inflation rate in Algeria during the period 1991-2023. The data was collected based on the database of the World Bank and the Bank of Algeria. The study concluded that there is no direct relationship between the exchange rate and the inflation rate in Algeria. The reason for this is due to the nature of the exchange system (managed float system) adopted as well as administrative intervention in the exchange market.